1985
DOI: 10.1252/jcej.18.450
|View full text |Cite
|
Sign up to set email alerts
|

Pressure distribution in a two-roll mill.

Abstract: An asymmetric pressure distribution in a pair of rolls rotating at equal and unequal speed for Newtonian fluid was obtained by lubrication model analysis and was compared with experimental values. The work was carried out with a pair of rolls of radius /?=8.2cm in the range of fluid viscosity \i=1.5-15Pa s, half of minimumnip clearance h0 =35-390/an, meanroll speed um=0.26-1.56m/s and roll speed ratio Nr=0.5-1. The experimental pressure profiles and force separating rolls are well represented by the calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Although good agreement was found between the theoretical and experimental results, the model was suitable for predicting the maximum positive pressure in the nip, but not in the subambient region. Murakami et al (1985) reported the development of a model for the prediction of pressure based on lubrication theory. They were capable of predicting the pressure between counterrotating rolls at low speed with Newtonian fluids.…”
Section: Introductionmentioning
confidence: 99%
“…Although good agreement was found between the theoretical and experimental results, the model was suitable for predicting the maximum positive pressure in the nip, but not in the subambient region. Murakami et al (1985) reported the development of a model for the prediction of pressure based on lubrication theory. They were capable of predicting the pressure between counterrotating rolls at low speed with Newtonian fluids.…”
Section: Introductionmentioning
confidence: 99%